Identification of Dried Fish Seller Income: Study Focus on Household Businesses in Bontang Kuala - Wijaya, Adi; Hasid, Zamruddin; Busari, Arfiah (Sangia Research Media and Publishing, 2023)
East Kalimantan is a province with one of the longest coastlines in Indonesia. For this gift, this paper tries to discuss the volume of income from the dry fish business cluster managed by households in Bontang Kuala. The method designed to process data was supported by a questionnaire that invited fish sellers in Bontang Kuala. The sample is limited and only focuses on involving 18 key informants because they are considered to meet the criteria, have broad insight about the proposed questionnaire, and are experienced. To support this, notebooks, recording devices, and questionnaire guides are needed that contain question items. Using two approaches, i.e. the identification of net income and gross income, this work presents two important points. First, the average net income reaches IDR 4,033,004 per month with an average cost of capital of IDR 1,689,218 per month. Second, the average gross income is IDR 5,722,222 per month which is obtained from the average price of dried fish IDR 37,279 per pcs and the quantity of products sold reaches an average of 155 pcs per month. Thus, a series of analyzes that function to prove or assess the level of income is simple and becomes an alternative that can be implemented by traders. Through the channel of the projection stage, it will provide knowledge and insight about the outcomes, implications, and limitations of the papers discussed in the future.